Three-dimensional greening landscape design device - YANG MENGLAN; ZHANG HUAWEI; LUO WEI (2020)
The utility model provides a three-dimensional greening landscape design device which comprises a fixed base and a greening planting disc, a supporting frame is arranged at the top of the fixed base,a supporting plate is arranged at the top of the supporting frame, a hidden frame is arranged at the top end of the supporting plate, and the greening planting disc is arranged at the top of the hidden frame. According to the greening device, through mutual cooperation of the flow guide plate arranged at the top of the greening planting disc and the infiltration holes, rainwater collected in rainydays can enter the water storage cavity through the infiltration holes to be stored in a centralized mode in the using process of the greening device, and through mutual cooperation of the water supply groove and the water absorption rope, rainwater can be collected in rainy days; according to the device, a rainwater recycling and automatic adsorbing mode is adopted, so that waste of water resources can be effectively avo